FACTUAL REFLECTION OF URBAN SPACE IN WILLIAM DEAN HOWELLS'S SHORT PROSE - Fesyanova, Natalia L.; Khuzina, Ekaterina A. (Gênero & Direito, 2019)
American writer William Dean Howells led an intensive search for artistic means to represent reality throughout his creative journey. His creative method was characterized by an acute sensation of the world's objectivity and the understanding of art as a special language. In this article, various types of art (landscape, music) are examined by which the writer created a factographic reflection of the urban space that determined the artistic specifics of his works. The theme of the city and the motive of the road in W. D. Howells creative destiny became fundamental ones and were reflected in his small prose. The studied texts of the American writer focused the attention on the inner world and the feelings of the author-narrator. He has a phenomenal memory that helps to save not only the experienced events, but also the emotional fabric of his wanderings in detail. The urban pictures conveyed by W.D. Howells are as detailed as possible, demonstrate both the author's picture of the world and the specific norms of the urban space of the XIXth century. In the stories the writer shows such power of the urban environment, which adversely affects the development of urban culture, not only ecological but also psychological pollution occurs, the break with the surrounding reality and the construction of an artificial world. Thus, it allowed the author to combine documentality and artistic generalizations, confirming everything with specific names, titles, and events. Throughout the narrative in the small prose by W. D. Howells, the idea of the organic development of small towns and the existence in harmony with the surrounding natural environment is the main one, which is of enormous importance for the modern world. An original translation from English in the article was performed by the author.